Search for new resonances in mass distributions of jet pairs using 139 fb-1 of pp collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Henkelmann, Lars; Jongmanns, Jan; Klassen, Martin; Krishnan, Anjali; et al. (Journal of high energy physics, 2020)
A search for new resonances decaying into a pair of jets is reported using the dataset of proton-proton collisions recorded at $$ \sqrt{s} $$ = 13 TeV with the ATLAS detector at the Large Hadron Collider between 2015 and 2018, corresponding to an integrated luminosity of 139 fb−1. The distribution of the invariant mass of the two leading jets is examined for local excesses above a data-derived estimate of the Standard Model background. In addition to an inclusive dijet search, events with jets identified as containing b-hadrons are examined specifically. No significant excess of events above the smoothly falling background spectra is observed. The results are used to set cross-section upper limits at 95% confidence level on a range of new physics scenarios. Model-independent limits on Gaussian-shaped signals are also reported. The analysis looking at jets containing b-hadrons benefits from improvements in the jet flavour identification at high transverse momentum, which increases its sensitivity relative to the previous analysis beyond that expected from the higher integrated luminosity.